(untitled) (The International Journal of Educational Sciences and Arts, 2025)
This study aims to deconstruct and analyze the strategies of influence and ideological extension of extremist discourse in the Arab context, taking the Houthi "Believing Youth" movement (Ansar Allah) in Yemen as a case study. Amidst the geopolitical and ideological transformations in the region, the Houthi movement has emerged as an influential actor whose power is not limited to its military dimension but extends to the construction of an integrated ideological and media ecosystem aimed at mobilization and reshaping collective consciousness. The study employs a qualitative methodology centered on Multimodal Critical Discourse Analysis (MCDA), examining a purposive sample of primary materials including televised speeches of the movement’s leader, Abdul-Malik al-Houthi, media content from the Al-Masirah network, official statements from the Political Bureau, and digital activity on the X and Telegram platforms. The findings reveal that Houthi discourse is based on a dual strategy that combines the invocation of a local religious-historical heritage (Jaroudi Zaydism and the doctrine of divine right to rule) with the utilization of a narrative of grievance (Maẓlūmiyyah) and resistance borrowed from the regional "Axis of Resistance" model. The analysis also shows that the movement’s media machine operates on a "Hub-and-Spoke" model, where encrypted platforms like Telegram serve as a hub for disseminating pure ideological content, while open platforms like X function as spokes to adapt and direct this discourse to a wider global audience. The study concludes that the movement’s effectiveness lies not only in its military strength but in its superior ability to produce and propagate a coherent discourse that grants religious and political legitimacy to its actions, posing a profound challenge that transcends conventional security-based approaches